Targeted adjustment of the posterior tibial slope in unicompartmental knee arthroplasty is feasible without altering the medial proximal tibial angle - Moses K. D. El Kayali; Rosa Berndt; Clemens Gwinner; Lorenz Pichler (Journal of Experimental Orthopaedics, 2025)
Abstract Purpose Recommendations regarding the surgical modification of the medial posterior tibial slope (mPTS) in medial unicompartmental knee arthroplasty (UKA) vary. Given the high preoperative variability, this often results in a significant change in the patient's mPTS through UKA. However, it is unclear whether this change in mPTS impacts the coronal alignment, specifically the medial proximal tibial angle (MPTA). Therefore, the purpose of this study was to report on the preoperative to post‐operative changes in mPTS and MPTA and their potential correlation in UKA. Methods Pre‐ and post‐operative radiographs of 96 consecutive patients undergoing conventional medial UKA were analyzed. Pre‐ and post‐operative mPTS and MPTA were measured on radiographs by two observers and reported. Their differences, as well as the difference from the target value of 7°, were analyzed. Cases were grouped regarding their mPTS change into cases with <3° and cases with ≥3° mPTS change, and the correlation between changes in mPTS and changes in MPTA was reported. Results The mean mPTS was reported at 9.27° (standard deviation [SD], 3.41°) preoperatively and 7.25° (SD, 2.23°) post‐operatively, with a mean change of −2.02° (SD, 3.84°; p < 0.001). Overall, 71.7% of cases had a post‐operative mPTS within ±2° of 7° without significant difference from the target value of 7° (p = 0.797). At a mean preoperative MPTA of 85.39° (SD, 2.34°) and a mean post‐operative MPTA of 84.12° (SD, 2.55°), UKA resulted in an average change of MPTA of −1.28° (SD, 2.55°; p < 0.001). Correlation coefficients revealed very weak correlations between the change in mPTS and the change in MPTA for all groups (r < −0.13 in all). Conclusions Targeted mPTS modification can be achieved, which implies a significant change from preoperative mPTS values in patients undergoing UKA. However, the change in mPTS does not affect the change in MPTA. Level of Evidence Level III.